Non -Linearities of optical fiber affecting modern communication system: An Overview - Dixit, Pragati (International Journal of Psychosocial Rehabilitation, 2021)
In recent years, even after the installation of erbium-doped fiber amplifiers, which have a higher bit rate transmission usually suited for transoceanic communication, people’s demand for higher data transmission capacity is unprecedented and growing continuously. The paper is presented in the form of an overview, addressing all the non-linear effects encountered in fiber and the advantages and disadvantages it will have on optical telecommunication. Topics covered are the types of non-linear effects that occur under non-linear scattering and changes in refractive index whenever the beam interacts with various components inside the optical fiber